Erosion of tungsten marker layers in W7-X. (2nd December 2021) - Mayer, M; Balden, M; Brezinsek, S; Dhard, C P; Elgeti, S; Fajardo, D; Fellinger, J; Guitart Corominas, M; Hiret, P; Kandler, M; Krause, M; Loesser, D; et al.
Abstract: In order to get first insight into net tungsten erosion in W7-X, tungsten (W) marker layers were exposed during the operational phase OP 1.2b at one position of the Test Divertor Unit (TDU), at 21 different positions of the inner heat shield, and at two scraper elements. The maximum tungsten erosion rate at the TDU strike line was 0.13 nm s −1 averaged over the whole campaign. The erosion was inhomogeneous on a microscopic scale, with higher erosion on ridges of the rough surface inclined towards the plasma and deposition of hydrocarbon layers in the recessed areas of the rough surface. The W erosion at the inner heat shield was below the detection limit of 3–6 × 10 12 W-atoms/cm 2 s, and all inner heat shield tiles were covered with a thin B/C/O layer with thickness in the range 2 × 10 17 –10 18 B + C atoms/cm 2 (about 20–100 nm B + C). W-erosion of the marker layers on the scraper elements was also below the detection limit.